Characterization of phase transformations and shape memory behavior of Fe-27.79Mn-2.72Si (wt%) alloy by thermomechanical and thermal treatments - Eskil, Murat; Ceylan, Mehmet (Springer, 2009)
Magnetic properties and volume fraction of the phases of a Fe-27.79Mn-2.72Si (wt%) alloy have been investigated by Mossbauer spectroscopy. The microstructure has been investigated using transmission electron microscope, scattering electron microscope, and light optical microscope. The stress-induced martensitic transformation, shape memory behavior, and shape recovery processes have been studied through the differential scanning calorimetry (DSC), tensile, and bending tests. The specimen was treated by the repetition of small amount of tensile deformations at room temperature, followed by a subsequent annealing at 600 A degrees C at every cycle for bending and tensile tests. During the tensile tests, Vickers hardness values were determined for every step of thermomechanical treatments. At low deformation rate, the shape memory effect is almost complete Bergeon et al. (A242:87, 1998), so low deformation rate was studied in this work. Bending test was another thermomechanical training procedure to see the recovery rate for this investigation.
Keywords: Mn-Si Alloys; Fcc/Hcp Martensitic-Transformation; Remarkable Improvement; Thermodynamic Analysis; Mechanical-Properties; Epsilon-Martensite; Alpha'-Martensite; Stainless-Steel; Stress; Microstructure